Precarisation, individualisation and the development of trade unions in Germany - Thore Beckmann; Xhulia Likaj; Paul Steimer; Michael Stöckel (Hochschule für Wirtschaft und Recht Berlin, Institute for International Political Economy (IPE), 2019)
Individualisation and precarisation as two broad trends in contemporary industrialised societies are related to one another and to certain developments in the German trade union landscape. With a focus on a reunified Germany from the nineties onwards, in this paper the impact of individualisation and precarisation on the state of trade unions is analysed. These processes are confluent and contribute to a diminishing influence of trade unions on the shape of industrial relations. In general, the neoliberal age brought about a competitive environment to which individuals are adapting. Nonetheless individualisation, on the one hand, induces mobility and selfdetermination for a fraction of workers who may no longer be represented by unified trade unions. The precarised and outsourced workforce, on the other hand, is deprived of life choices and has difficulties to organise in a conventional manner, even more so in an environment of asymmetric developments between labour market trends and membership structures in trade unions. Hence, it can be argued that these major trends endure an erosion of collective solidarity which has been the basis of a Fordist employment relationship.
Keywords: 330; Individualisation; Precarisation; Germany; Trade Unions; Industrial Relations; Labour Market